Schema theory: a critical appraisal and reevaluation - Shea, C. H.; Wulf, G. (Journal of Motor Behavior, 2005)
The authors critically review a number of the constructs and associated predictions proposed in schema theory (R. A. Schmidt, 1975). The authors propose that new control and learning theories should include a reformulated (a) notion of a generalized motor program that is not based on motor program but still accounts for the strong tendency for responses to maintain their relative characteristics; (b) mechanism or processes whereby an abstract movement structure based on proportional principles (e.g., relative timing, relative force) is developed through practice; and (c) explanation for parameter learning that accounts for the benefits of parameter variability but also considers how variability is scheduled. Furthermore, they also propose that new theories of motor learning must be able to account for the consistent findings spawned as a result of the schema theory proposal and must not be simply discounted because of some disfavor with the motor program notion, in general, or schema theory, more specifically.